2017
DOI: 10.3945/ajcn.116.147603
|View full text |Cite
|
Sign up to set email alerts
|

The SLC2A14 gene, encoding the novel glucose/dehydroascorbate transporter GLUT14, is associated with inflammatory bowel disease

Abstract: Background: Variations in intestinal antioxidant membrane transporters are implicated in the initiation and progression of inflammatory bowel disease (IBD). Facilitated glucose transporter member 14 (GLUT14), encoded by the solute carrier family 2 member 14 (SLC2A14) gene, is a putative transporter for dehydroascorbic acid and glucose. Although information on the gene is limited, shorter and longer GLUT14 isoforms have been identified. We hypothesized that GLUT14 mediates glucose and dehydroascorbic acid uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Previous studies have revealed that genetic variations in Slc2a14 are involved in the development and progression of chronic diseases, including inflammatory bowel disease (IBD) and Alzheimer's disease (37-39). The facilitated glucose transporter 14 encoded by SLC2A14 promotes the development of IBD and may be applied for precision intervention of IBD (38). SLP-2 belongs to the stomatin protein family, plays a critical role in T cell activation and is a candidate target for immunomodulation (40).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that genetic variations in Slc2a14 are involved in the development and progression of chronic diseases, including inflammatory bowel disease (IBD) and Alzheimer's disease (37-39). The facilitated glucose transporter 14 encoded by SLC2A14 promotes the development of IBD and may be applied for precision intervention of IBD (38). SLP-2 belongs to the stomatin protein family, plays a critical role in T cell activation and is a candidate target for immunomodulation (40).…”
Section: Discussionmentioning
confidence: 99%
“…GLUT3 is mainly present in the brain [ 11 ]. A GLUT3 variant (GLUT14) has also been found in the genome as a duplicon of GLUT3 [ 12 ], but is essentially uncharacterised and of unknown function and tissue distribution, although there is some disease association [ 13 ]. GLUT2 and GLUT3 have K m values for glucose transport that are higher and lower, respectively, than fasting blood glucose reflecting the functions of these proteins in supplying glucose (GLUT2) and rapidly and avidly removing glucose (GLUT3) from the circulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, other glucose transporters, including SLC2A10 (GLUT10) and SLC2A14 (GLUT14), were significantly downregulated. A previous study hypothesized that genetic variations in SLC2A14 may be associated with inflammatory disease [73]. Also, SLC2A10 was found to be associated with T2D [74,75].…”
Section: Discussionmentioning
confidence: 96%